Time trends towards earlier puberty in boys and girls with type 1 diabetes: Insights from the German Diabetes Prospective Follow-up (DPV) registry, 2000 to 2021 - Gohlke, Bettina; Reschke, Felix; Lanzinger, Stefanie; Boettcher, Claudia; Gemulla, Gitta; Thiele-Schmitz, Susanne; Dunstheimer, Désirée; van den Boom, Louise; Wölfle, Joachim; Holl, R. W. (Diabetes Obesity & Metabolism, 2023)
Aim: To examine the time trends and factors associated with the onset of puberty in children with type 1 diabetes (T1D) using data from the German Diabetes Prospective Follow-up (Diabetes-Patienten-Verlaufsdokumentation [DPV]) registry. Methods: A total of 13 127 children with T1D, aged 6 to 18 years, were included in the analysis. Regression analysis was performed to investigate the relationship between diabetes duration, body mass index (BMI) standard deviation score (SDS), glycated haemoglobin (HbA1c) level, migration background, and the onset of puberty, stratified by sex. Results: Our findings revealed a significant trend towards earlier puberty in both girls and boys with T1D over the observed period (2000 to 2021). Puberty onset in girls (thelarche Tanner stage B2) decreased from 11.48 (11.35-11.65) years in 2000 to 10.93 (10.79-11.08) years in 2021 and gonadarche (Tanner stage G2/testicular volume >3 mL) decreased from 12.62 (12.42-12.82) years in 2000 to 11.98 (11.79-12.16) years in 2021 in boys (both P < 0.001). Longer diabetes duration, higher BMI SDS, and lower HbA1c level were associated with earlier puberty in both sexes (P < 0.001). Conclusions: Our study highlights earlier puberty in children with T1D, influenced by BMI SDS, HbA1c level, and migration background. This has important implications for diabetes management and supporting healthy development. Further research is needed to understand the underlying mechanisms and develop potential interventions for this vulnerable population.
CRIS-Team Scopus Importer:2023-10-20
Keywords: body composition; clinical physiology; cohort study; type 1 diabetes